Marketing You - Joy Cantrell Jordan (EDIS)
The purpose of this Florida 4-H Recognition Portfolio is to help you review and reflect on your previous 4-H experiences, recognize the skills and accomplishments you have acquired from these activities and learn to market yourself as a result of these experiences. Printed January 1994. Revised August 2002.